Synthesis of Cellulose Nanofiber from Palm Oil Empty Fruit Bunches Using Acid Hydrolysis Method (Universitas Negeri Semarang, 2022)
Nanocellulose comes in a variety of forms, the most common are fibrils or fibers, which contribute to its application in biodegradable products. Because cellulose nanofibers (CNF) have a high strength-to-weight ratio and are biodegradable, they play a significant role in the development of novel materials such as biopolymers. Oil palm empty fruit bunches, which are commonly available in East Kalimantan, were used to make cellulose nanofibers in this research. Other components included in raw materials, such as lignin and hemicellulose, can be removed to isolate the cellulose. The chemical method was chosen over the others since it has been proved to be effective in the isolation of nanocellulose. The composition and morphology of the CNF samples were next examined using FT-IR, SEM, and XRD. From the characterization results, it was found that the size of the nanocellulose fibers ranged from 400 nm - 900 nm. The high crystallinity level of 65% indicates high thermal stability so the CNF can be used for various matters. The results of the FT-IR test showed a peak around 1000-1100 cm-1 which indicated the vibration of the skeletal C-O-C pyranose ring that contributed to the increase in the crystallinity of CNF.